Solid-density plasma characterization with x-ray scattering on the 200 J Janus laser - Neumayer, P; Gregori, G; Ravasio, A; Koenig, M; Price, D; Widmann, K; Bastea, M; Landen, O; Glenzer, S (2006)
We present collective x-ray scattering (CXS) measurements using a chlorine He-alpha x-ray source pumped with less than 200 J of laser energy. The experimental scattering spectra show plasmon resonances from shocked and radiatively heated samples. These experiments use only 10(12) x-ray photons at the sample of which 10(-5) have been scattered and detected with a highly efficient curved crystal spectrometer. Our results demonstrate that x-ray scattering is a viable technique on smaller laser facilities, making CXS measurements accessible to a broad scientific community. (c) 2006 American Institute of Physics.